Saturated Hydraulic Conductivity of Nine Soils According to Water Quality, Soil Texture, and Clay Mineralogy - Clarissa Buarque Vieira; Gabriel Henrique Maximo Clarindo Silva; Brivaldo Gomes de Almeida; Luiz Guilherme Medeiros Pessoa; Fernando José Freire; Valdomiro Severino de Souza Junior; Hidelblandi Farias de Melo; Luara Gabriella Gomes de Lima; Rodrigo Francisco do Nascimento Paiva; Jorge Freire da Silva Ferreira; Maria Betânia Galvão dos Santos Freire (Agronomy)
Water quality affects soils by promoting their degradation by the accumulation of salts that will lead to salinization and sodification. However, the magnitude of these processes varies with soil attributes. Saturated hydraulic conductivity (Ksat) is the rate at which water passes through saturated soil, which is fundamental to determining water movement through the soil profile. The Ksat may differ from soil to soil according to the sodium adsorption ratio (SAR), water electrical conductivity (ECw), soil texture, and clay mineralogical assemblage. In this study, an experiment with vertical columns and constant-load permeameters was conducted to evaluate changes in soil Ksat with waters comprising five ECw values (128, 718, 1709, 2865, and 4671 µS cm−1) and five SAR values [0, 5, 12, 20, and 30 (mmolc L−1)0.5] in combination. Horizons from nine northeastern Brazilian soils (ranging from tropical to semiarid) were selected according to their texture and clay mineralogical composition. The data obtained were fit with multiple regression equations for Ksat as a function of ECw and SAR. This study also determined the null SAR at each ECw level, using Ksat = 0 on each equation, to predict the SAR needed to achieve zero drainage on each soil for each ECw level and the threshold electrolyte concentration (CTH) that would lead to a 20% reduction of maximum Ksat. Neither the ECw nor SAR of the applied waters affected the Ksat of soils with a mineralogical assemblage of oxides and kaolinite such as Ferralsol, Nitisol, and Lixisol, with an average Ksat of 2.75, 6.06, and 3.33 cm h−1, respectively. In smectite- and illite-rich soils, the Ksat increased with higher ECw levels and decreased with higher SAR levels, especially comparing the soil’s estimated Ksat for water with low ECw and high SAR in combination (ECw of 128 µS cm−1 and SAR 30) and water with high ECw and low SAR in combination (ECw of 4671 µS cm−1 and SAR 0) such as Regosol (4.95 to 10.94 cm h−1); Vertisol (0.28 to 2.04 cm h−1); Planosol (0 to 0.29 cm h−1); Luvisol (0.46 to 2.12 cm h−1); Cambisol (0 to 0.23 cm h−1); and Fluvisol (1.87 to 3.34 cm h−1). The CTH was easily reached in soils with high concentrations of highly active clays such as smectites. In sandy soils, the target CTH was only reached under extremely high SAR values, indicating a greater resistance of these soils to salinization/sodification. Due to their mineralogical assemblage, soils from tropical sub-humid/hot and semiarid climates were more affected by treatments than soils from tropical humid/hot climates, indicating serious risks of physical and chemical degradation. The results showed the importance of monitoring water quality for irrigation, mainly in less weathered, more clayey soils, with high clay activity to minimize the rate of salt accumulation in soils of the Brazilian semiarid region. Our study also proved that clay mineralogy had more influence on the Ksat than clay concentration, mainly in soils irrigated with saline and sodic waters, and that soils with highly active smectite are more prone to degradation than soils with high concentrations of kaolinite.